Meningkatkan Kesadaran Remaja Terhadap Phishing Melalui Literasi Digital: Studi Kasus di SMK Darussalam Makassar - Arsyad, Andi Asyhary J.; Tamrin, Usman; Lande, Janisa Pascawati; Umar, Najirah (Jurnal Pengabdian Literasi Digital Indonesia, 2024)
Phishing attacks are among the most common and damaging cybersecurity threats, exploiting human vulnerabilities such as a lack of awareness and digital literacy. This study aims to identify effective strategies for increasing awareness of phishing attacks through digital literacy among teenagers. The research was conducted at SMK Darussalam Makassar using a descriptive quantitative method and involved 227 respondents. The findings indicate that 80% of respondents agree that digital literacy plays a significant role in reducing the impact of phishing. Digital literacy, which includes understanding technology, identifying threats, and taking protective measures, has proven effective in protecting students from phishing attacks. Based on the Protection Motivation Theory (PMT), awareness of phishing threats and the effectiveness of protective actions increase students' motivation to protect themselves. This study recommends the development of sustainable digital literacy programs, policies to reduce unnecessary internet usage, and the blocking of access to harmful websites. By improving digital literacy, the community, especially teenagers, will be better prepared to face cyber threats and safeguard their personal information.